A new species of dwarf chameleon (Sauria; Chamaeleonidae, Bradypodion Fitzinger) from KwaZulu Natal South Africa with notes on recent climatic shifts and their influence on speciation in the genus - Tilbury, Colin R.; Tolley, Krystal A. (Zootaxa, 2009)
A new species of dwarf chameleon is described from a restricted patch of relict indigenous forest in KwaZulu-Natal (KZN), South Africa. Its specific status is confirmed by phylogenetic analyses using molecular markers (1390 bp of mitochondrial 16S and ND2). The node defining this species is highly supported with both analyses (100% posterior probability, 100% bootstrap support). This species (Bradypodion ngomeense sp. nov.) is part of a larger clade of forest species, but is itself confined to a single forest (Ngome Forest). The molecular patterns of other forest restricted species in KZN were examined with a view to elucidate their patterns of distribution. It is postulated that these patterns may be the result of climatic shifts during the Pleistocene on the extent of forest cover which afforded multiple contact opportunities between coastal and montane forest elements with possible opportunities for gene flow between forests. At present, these patches are under threat from human activities such as forest resource extraction, sugar cane and pine plantations. Their small distributions and possibility for future habitat loss make these species of conservation concern. The taxonomic status of a recently described species Bradypodion nkandlae (Raw & Brothers 2008) is found to be conspecific with B. nemorale and is herewith synonymised.